The Influence of Online Learning Using the Zoom Application Media on the Learning Outcomes of Educational Technology Students Unim Bone - Muldiyana, Muldiyana; Ihsan, Ahmad Nurul; Faslan, Zul (Jurnal Ilmiah Mandala Education (JIME), 2023)
This research aims to determine the effect of online learning using zoom media on student learning outcomes, either partially or simultaneously. This research is quantitative research with an ex post facto design, aiming to determine the influence on economics subjects using an online learning system. The ex post facto method aims to be able to find possible causes of changes in behavior, symptoms, or events caused by an event that can cause changes in variables that have occurred as a whole. Data collection techniques are primary data and secondary data. The technique for analyzing data in this research uses quantitative data obtained from questionnaires, which will be processed using simple regression analysis using SPSS Statistics 24 software. Online learning using zoom media on student learning outcomes has a positive and significant influence with a large influence of 0.001 < 0, 05. This means that online learning using zoom media has an influence or improvement on learning outcomes in lessons